2012
DOI: 10.1161/circep.111.964262
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation of Right Atrial Ganglionated Plexi in Patients With Vagal Paroxysmal Atrial Fibrillation

Abstract: Background— Catheter ablation of ganglionated plexi (GP) in the left atrium has been proposed in different subgroup of patients with atrial fibrillation (AF). Anatomic studies found a high prevalence of GP in the posterior surface of the right atrium (RA). Experimental data suggested the potential role of right atrial GP in the AF initiation and maintenance. The aim of our study was to assess the efficacy of GP ablation in RA in patients with vagal AF. Methods and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 45 publications
1
59
0
1
Order By: Relevance
“…9,14 However, an animal study 27 reported ablation of the right pulmonary vein-atrial junction fat pads facilitated rather than prevented the initiation of AF. Another clinical study assessed the long-term outcome of patients who underwent anatomic GP ablation for paroxysmal AF, 29 results demonstrated that anatomic GP ablation could only achieve short-term suppression of AF inducibility; however, this result was not maintained over the long-term.…”
Section: Changes In the Electrophysiological Characteristics In The Tmentioning
confidence: 99%
See 1 more Smart Citation
“…9,14 However, an animal study 27 reported ablation of the right pulmonary vein-atrial junction fat pads facilitated rather than prevented the initiation of AF. Another clinical study assessed the long-term outcome of patients who underwent anatomic GP ablation for paroxysmal AF, 29 results demonstrated that anatomic GP ablation could only achieve short-term suppression of AF inducibility; however, this result was not maintained over the long-term.…”
Section: Changes In the Electrophysiological Characteristics In The Tmentioning
confidence: 99%
“…For example, Oh et al 12 reported that radiofrequency ablation of fat pads may not achieve long-term suppression of AF induction in a canine model. By contrast, Pokushalov et al 13 and Calo et al 14 confirmed that GP ablation in humans could be an efficient treatment for AF.…”
mentioning
confidence: 96%
“…34 It has been suggested that ganglionated plexi may have a role in the initiation and maintenance of both paroxysmal and non-paroxysmal AF. [35][36][37][38][39][40][41] Localisation is usually performed on the endocardium either anatomically, by vagal response following high-frequency stimulation, or by Fourier transform in sinus rhythm. 35,37 Although ganglionated plexi ablation significantly reduces AF recurrence, the long-term success rate is lower than after PVI.…”
Section: Pathophysiology Of Atrial Fibrillation and Atrial Fibrillatimentioning
confidence: 99%
“…[35][36][37][38][39][40][41] Localisation is usually performed on the endocardium either anatomically, by vagal response following high-frequency stimulation, or by Fourier transform in sinus rhythm. 35,37 Although ganglionated plexi ablation significantly reduces AF recurrence, the long-term success rate is lower than after PVI. [35][36][37][38][39][40][41] Interestingly, in addition to PVI, the suppression of ganglionated plexi response -particularly that observed during cryoablation -may reduce AF recurrence.…”
Section: Pathophysiology Of Atrial Fibrillation and Atrial Fibrillatimentioning
confidence: 99%
See 1 more Smart Citation